The directions of Philippine publishing and the development of Filipiniana collections of selected university libraries in Metro Manila - Pulanco, Elizabeth T. (1995)
This study was conducted to determine the present status and directions of Philippine publishing, the publishers' activities and strategies in promoting appreciation of Filipiniana materials and the problems they have encountered in the production, promotion and handling of these materials and how these affect the Filipiniana collection building. This study also seeks to ascertain the methods and criteria used by fourteen selected university librarians in their selection and acquisition of Filipiniana materials and the problems they encounter.